Factors Motivating Participation of Persons with Disability in the Philippines: The Discount Privilege in Goods and Services - Aubrey D. Tabuga (Philippine Institute for Development Studies (PIDS), 2010)
In urban Philippines, the percentage of persons with disability (PWDs) participating in various government and nongovernment programs is low. In fact, the level of awareness among PWDs on the policies that intend to uplift their well-being is also low. These were some of the findings of a 2008 survey on persons with disability in selected cities in Metro Manila. This paper therefore aims to examine this problem by looking at the various factors that influence the PWD's participation specifically in the government-mandated discount on fare on bus and other land transportation vehicles and medical services. Interestingly, it focuses on the role of social networks among PWD, environmental constraints, and the type of disability the person has. Interestingly, because participation is conditional on awareness and eligibility, this paper likewise looks into variables that are associated with awareness and eligibility. The goal is to identify areas of potential gaps in terms of information dissemination, implementation, and enforcement so that PWDs can fully benefit from the policies and programs intended for them. This paper uses the dataset of a pioneering survey on 400 PWDs conducted in 2008 in Metro Manila.
Keywords: 330; Philippines; disability; participation; Philippine survey on PWD; Behinderte Arbeitskräfte; Erwerbstätigkeit; Manila; Philippinen